DIAGNOSIS OF NONPALPABLE BREAST CANCER IN PREMENOPAUSAL WOMEN - N. V. Nudnov; E. V. Novikova (Вестник рентгенологии и радиологии, 2017)
Objective: to analyze the possibilities of standard and additional methods for X-ray mammography (MG) in the comprehensive diagnosis of nonpalpable breast masses and preclinical cancers; to identify the important radiological signs of malignancy as predictors for the application of multislice spiral computed tomography/ magnetic resonance imaging (MSCT/MRI-MG), as well as invasive studies in premenopausal women. Material and methods. The investigation enrolled 423 pre-menopausal patients with nonpalpable breast masses; 129 women were found to have breast cancer. The diagnosis was verified by comprehensive clinical and instrumental examination using standard and additional methods for X-ray mammography, ultra-sonography, MRI, MSCT of the breast and biopsy. Significant radiological signs of malignancy of the lesions were detected and their diagnostic value was identified.Results. The use of additional diagnostic techniques for mammography contributes to the confident visualization of important radiological criteria for malignancy, enhances the informative value of by 5%, and promotes a decline in the number of unjustified biopsies by 11%. Conclusion. Problems in visualizing and categorizing nonpalpable breast masses necessitate additional diagnostic techniques for X-ray mammography. The identification and confident interpretation of important radiological criteria for benign or malignant lesions increase the diagnostic value of X-ray mammography: the sensitivity from 91% to 98%, specificity from 61% to 75%. MSCT-MG and MRI-MG demonstrate even higher efficiency: contrast-enhanced (CE) MSCT–MG (100% sensitivity, 99% specificity) and CE MRI–MG (100% sensitivity, 98% specificity). Sequential radiological and morphological studies improve the quality and efficiency of diagnosis of nonpalpable breast cancer.